5‐Aminoimidazole‐4‐carboxamide 1‐β‐D‐ribofuranoside reduces intimal hyperplasia of tissue engineering blood vessel by inhibiting phenotype switch of vascular smooth muscle cell. Issue 4 (7th January 2016) - Wu, Yangxiao; Liu, Ge; Chen, Wen; Yang, Mingcan; Zhu, Chuhong
Abstract: Intimal hyperplasia (IH) is the cause of clinical failure in patients with vascular transplants and intravascular stents. The proliferation and phenotype switching of vascular smooth muscle cells (VSMCs) play important roles in IH. Inhibiting the proliferation of VSMCs and maintaining the differentiated phenotype of VSMCs is one way to reduce IH. In this article, 5‐aminoimidazole‐4‐carboxamide 1‐β‐D‐ribofuranoside (AICAR) was used in experiments after drug screening. We found that the metabolism, autophagy, and differentiation of VSMCs were enhanced which were important to the normal function of VSMCs, but the secretion of VSMCs was reduced after AICAR treatment. AICAR induces G1 phase arrest and inhibits the proliferation of VSMCs using the MTT and EdU assays and cell cycle analysis. Then, the rat carotid artery vessel transplantation model was used to evaluate the function of AICAR in vivo . AICAR‐modified tissue‐engineered blood vessels (TEBVs) had a higher patency rate and less IH than the control TEBVs. In conclusion, AICAR can improve the normal function of VSMCs by increasing the metabolism and autophagy of VSMCs but inhibit the proliferation, paracrine, and phenotypes switching of VSMCs, further contribute the reducing of IH in TEBVs. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 105B: 744–752, 2017.